Augmented reality: as a guidance and counseling tool for early childhood - Nasution, Nurliana (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
Learning in early childhood education institutions uses the method of playing while learning. Likewise in carrying out the guidance and counseling process, early childhood must be in a pleasant atmosphere. Augmented reality is one of the media that can be used as a play tool by children to achieve the goals of guidance and counseling carried out by the teacher. This study aims to design an augmented reality application that can be used by early childhood to describe real conditions for children to recover from trauma or excessive anxiety about an object. The research methodology used is development research with research stages namely need assessment, preparation of an augmented reality information system, conceptual and operational trials in three PAUDs in Pekanbaru, Riau, Indonesia. this research methodology describes the stages of the methodology applied in conducting research with reference to the software development cycle in the form of a waterfall model. The result is an augmented reality application that supports the guidance and counseling process in early childhood education institutions.